Enhanced piezoresponse of electrospun PVDF mats with a touch of nickel chloride hexahydrate salt - Dhakras, Dipti; Borkar, Vivek; Ogale, Satishchandra; Jog, Jyoti Prakash (Nanoscale, 2012)
PVDF nanofibers are prepared using electrospinning. The effect of addition of a hydrated salt, nickel chloride hexahydrate (NiCl2 center dot 6H(2)O), on the phase formation is examined. Addition of the hydrated salt (NC) is found to enhance the polar beta phase by about 30%. The peak to peak piezo-voltage generated for PVDF NC is almost 0.762 V, a factor of 3 higher than that for PVDF. The fiber mats exhibit a significantly enhanced dynamic strain sensor response. The voltage generated per unit micro-strain developed during the free vibration test for PVDF was 0.119 mV whereas it was 0.548 mV for PVDF NC, exhibiting a non-linearly enhanced performance vis a vis the increase in the beta phase component.

High performance all-organic flexural piezo-FET and nanogenerator via nanoscale soft-interface strain modulation - Dhakras, Dipti; Gawli, Yogesh; Chhatre, Shraddha; Wadgaonkar, Prakash; Ogale, Satishchandra (Physical Chemistry Chemical Physics, 2014)
Flexural strain fields are encountered in a wide variety of situations and invite novel device designs for their effective use in sensing, actuating, as well as energy harvesting (nanogenerator) applications. In this work we demonstrate an interesting all-organic device design comprising an electrospun P(VDF-TrFE) fiber-mat built directly on a conducting PANI film, which is also grown on a flexible PET substrate, for flexural piezo-FET and nanogenerator applications. Orders of magnitude stronger modulation of electrical transport in PANI film is realized in this device as compared to the case of a similar device but with a uniform spin-coated P(VDF-TrFE) film. We find that in the flexural mode of operation, the interaction between the laterally modulated nanoscale strain field distributions created by the fibers and the applied coherent strain field strongly influences the carrier transport in PANI. The transport modulation is suggested to occur due to strain-induced conformational changes in P(VDF-TrFE) leading to changes in carrier localization-delocalization. We further show that the fiber-mat based device system also works as an efficient nanogenerator capable of delivering power for low power applications.

3D Polyaniline architecture by concurrent inorganic and organic acid doping for superior and robust high rate supercapacitor performance - Gawli, Yogesh; Banerjee, Abhik; Dhakras, Dipti; Deo, Meenal S.; Bulani, Dinesh; Wadgaonkar, Prakash P.; Shelke, Manjusha; Ogale, Satishchandra (Scientific Reports, 2016)

High-performance organic-inorganic hybrid piezo-nanogenerator via interface enhancedpolarization effects for self-powered electronic systems - Dhakras, Dipti; Ogale, Satishchandra (Advanced Materials Interfaces, 2016)
An electrospun fi ber based wearable organic-inorganic hybrid piezonanogenerator compose of suitably engineered P(VDF-TrFE) and BaTiO3 nanostructures is reported. In the case of the device with an electrospun mat of piezoelectric beta-phase P(VDF-TrFE) and BaTiO3 nanoparticulates fi lled in the interfi ber open spaces, a power density of 16 mu W cm(-2) is realized at an applied impact of 0.02 MPa (which essentially corresponds to the thumb pressure). A similar device, with BaTiO 3 additionally embedded in the P(VDF-TrFE) fi bers during their formation, renders a signifi cantly higher peak power density of 28 mu W cm(-2) with instantaneous power density of approximate to 8.8 mu W cm(-2) at the same touch pressure. This performance is attributed to the high density of interfaces in such a device and the corresponding enhancement in the dielectric response. It is demonstrated that the power generated from such a hybrid device structure can be used for small scale applications such as charging a mobile phone.